Pendampingan dalam Membaca, Berpikir, dan Menulis Kritis pada Mahasiswa - Hermila A; Gita Juniarti; Ismaul Fitroh; Rahmat Taufik R.L. Bau; Muhammad Akram Mursalim (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Technology can help get work done, but the presence of technology also has the potential to reduce students' critical thinking because technology can complete student work, so students do not need to read and write. It encourages the community service team to carry out activities by critically assisting students in reading, thinking, and writing. The service is carried out using a PAR approach, starting with research about the relation of students' interest in reading and their critical thinking. It is used as a basis for socialization about scientific literacy. After it, the community service team held discussions, asked questions about the books the students had read, and encouraged students to write their critical thoughts into essays. The results showed that 49 students had completed scientific articles based on their critical thinking. This activity is in partnership with GRAIM Unity literacy community and was held from February to June 2023.